2001
DOI: 10.1097/00005768-200112000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Clothing fabric does not affect thermoregulation during exercise in moderate heat

Abstract: In summary, before, during, or after exercise in a moderately warm environmental condition, neither the addition of a modest amount of clothing nor the fabric characteristics of this clothing alters physiological, thermoregulatory, or comfort sensation responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
63
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 19 publications
9
63
1
Order By: Relevance
“…2a). The skin and rectal temperatures reported in the current study are similar to those reported by Gavin (2001). These authors showed no differences in these temperatures when wearing a synthetic clothing ensemble (short-sleeve T-shirt, cycling shorts) compared with being semi-nude (lycra swim suit) during submaximal exercise in 30°C.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…2a). The skin and rectal temperatures reported in the current study are similar to those reported by Gavin (2001). These authors showed no differences in these temperatures when wearing a synthetic clothing ensemble (short-sleeve T-shirt, cycling shorts) compared with being semi-nude (lycra swim suit) during submaximal exercise in 30°C.…”
Section: Discussionsupporting
confidence: 87%
“…2a). Indeed, Gavin (2001) has shown that thermoregulation was not negatively affected by 45 min of submaximal exercise consisting of running and walking with crew neck short sleeved T-shirt and cycling shorts at 30°C. Hence, it appears that the compression garment did Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be concluded that in the subjects wearing woolen clothing, the NA-ergic nervous mechanism predominates over the humoral A mechanism, while in the subjects wearing 100% acrylic clothes, a reverse reaction can be observed. The effect of different clothing material on HR during physical effort has been investigated by Kwon et al [26] who found higher HR values in individuals wearing synthetic (polyester) clothing than in those wearing cotton clothing, as well as by Gavin et al [10] who, however, did not observe any effect of the clothing fabric on HR in persons examined during physical effort. The findings of our study confirm that HR is intensified by wearing clothes made of synthetic fabric.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the clothing material on human physiological parameters is usually investigated in the context of the thermal stress that may be associated with physical effort. In general, it is believed that the properties of clothing can considerably change the physiological conditions related to physical effort [7,27], but it has not always been possible to provide evidence that they affect the thermoregulatory mechanisms [10]. Zimniewska proved that even under static conditions, the temperature measured on the skin surface depended on the kind of clothing and was higher when the subjects worn polyester clothes than the linen ones [12,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation